Trajectory Generation for Hip Rehabilitation Exoskeleton Using Trajectory - Sapiee, M.R.; Marhaban, M.H.; Miskon, M.F.; Ishak, A.J. (International Journal of Human and Technology Interaction (IJHaTI), 2020)
A walking rehabilitation exoskeleton robot is used for patient having walking difficulty to undergo walking therapy by wearing it on his lower body. If the rehabilitation is done directly by using  predefined normal gait, the patient can feel discomfort and may lead to painful therapy. This can also endangered the patient limb under therapy. Due to that reason, the patient will be discouraged and unmotivated to proceed with the therapy. This paper presents the hip trajectory generation by utilizing the patient current trajectory that morphs into the target trajectory by generating a sequence of gradually changing hip trajectories.